Disinfection by-products in Croatian drinking water supplies with special emphasis on the water supply network in the city of Zagreb. (15th December 2020) - Kurajica, L.; Ujević Bošnjak, M.; Novak Stankov, M.; Kinsela, A.S.; Štiglić, J.; Waite, D.T.; Capak, K.
Abstract: The occurrence of disinfection by-products (DBPs) was investigated in 48 drinking water systems across Croatia. Eleven DBPs were studied: chlorite (ClO2 − ), chlorate (ClO3 − ), four trihalomethanes (THMs), and five haloacetic acids (HAAs). Furthermore, an intensive sampling program was conducted in the distribution system in the city of Zagreb where, aside from DBP analyses, natural organic matter (NOM) was characterized using fluorescence spectroscopy. In the drinking waters examined across Croatia, DBP values were found in the range from 0.7 μg/L to 32.8 μg/L for THMs, below LOQ to 17.2 μg/L for HAAs (primarily di- and trichloroacetic acids), below LOQ to 720 μg/L for ClO2 − and below LOQ to 431 μg/L for ClO3 − . The results obtained showed higher chlorite concentrations in the systems treated with hypochlorite compared to systems treated with chlorine dioxide. DBPs in the Zagreb distribution network were generally low (the average values were below 6 μg/L and 2 μg/L for total THM and total HAA respectively). In contrast to our observations throughout Croatia, dibromoacetic acid (DBAA) was found to be the predominant HAA within Zagreb, most likely due to the degradation of chlorinated carboxylates (di-/tri-chloroacetic) in the network. Characterization of NOM by Parallel Factor Analysis (PARAFAC) fluorescence spectroscopy across the Zagreb network showed distinct temporal variations arising from groundwater inputs, as evident from variable humic-, tyrosine-, and tryptophan-like peaks. Statistical correlations between fluorescence data and DBPs highlight its potential for monitoring the presence of DBPs in distribution networks. Graphical abstract: Image 1 Highlights: Low levels of DBPs across Croatian water supply systems were observed. Groundwater-supplied networks contain lesser amounts of DBPs. Hypochlorite disinfection causes higher chlorate concentrations than chlorine dioxide. Di-/trihaloacetic acids degrade in larger water supply networks. Fluorescence techniques could be used for assessing likely presence of DBPs.